Trends in the development of mortgage–backed securities in modern condition - Sh. U. Niyazbekova; A. B Mottaeva; S. Yu. Eroshkin; M. G. Krishtal (Модернизация, инновация, развитие, 2022)
Purpose: to identify objective patterns of development of mortgage–backed securities that determine the prospects of this direction to increase its role in the Russian economy.Methods: the study used general scientific methods of cognition, including comparative analysis, economic–statistical and abstract– logical methods, generalization and complex analysis. The methodological basis is the fundamental provisions of the theory of mortgages, the general theory of mortgage lending, thematic works of domestic and foreign scientists, as well as data from the Analytical Center DOM.RF.Results: the concept and classification of mortgage–backed securities are considered, the features of securitization are presented. The analysis of factors affecting the price level and profitability of mortgage–backed securities is carried out. The analysis of the state of the mortgage securities market in Russia has been carried out. The analysis of factors that have a significant impact on the current level of prices and yields of Russian mortgage bonds has been carried out. Development problems have been identified.Conclusions and Relevance: in the conditions of uncertainty in the Russian economy caused by the pandemic, sanctions, geopolitical tensions and inflation, retail investors are seek to secure their savings by investing them in bonds with yields higher than deposit rates. Bank deposits will remain the main way of saving money for the population. The popularity of bond investments will gradually grow, especially among the younger generation. The state has taken the right step towards improving the financial literacy of the Russian population and instilling a culture of investing in various instruments, especially securities. A similar practice should be applied to mortgage–backed securities. It is recommended to use positive experience in attracting individuals to certain segments of the stock market: simplification of access and purchase of mortgage bonds for the ordinary population; information campaign to popularize mortgage bonds as a simple investment tool with optimal compliance with the «risk–return» parameters; provision of state or institutional support measures in the form of tax benefits for investors, or reduced size agency commissions.